An explanation of the mystifying bakanae disease narrative for tomorrow's rice - Shakeel, Qaiser; Mubeen, Mustansar; Sohail, Muhammad Aamir; Ali, Sajjad; Iftikhar, Yasir; Tahir Bajwa, Rabia; Aqueel, Muhammad Anjum; Upadhyay, Sudhir K.; Divvela, Praveen Kumar; Zhou, Lei (Frontiers in Microbiology, 2023)
Rice production is severely hampered by Bakanae disease (Fusarium fujikuroi), formerly recognized as F. moniliforme. F. moniliforme was called the F. fujikuroi species complex (FFSC) because it was later discovered that it had some separate species. The FFSC's constituents are also well recognized for producing phytohormones which include auxins, cytokinin, and gibberellins (GAs). The normal symptoms of bakanae disease in rice are exacerbated by GAs. The FFSC members are responsible for the production of fumonisin (FUM), fusarins, fusaric acid, moniliformin, and beauvericin. These are harmful to both human and animal health. This disease is common around the world and causes significant yield losses. Numerous secondary metabolites, including the plant hormone gibberellin, which causes classic bakanae symptoms, are produced by F. fujikuroi. The strategies for managing the bakanae illness, including the utilization of host resistance, chemical compounds, biocontrol agents, natural goods, and physical approaches, were reviewed in this article. Bakanae sickness is still not entirely prevented, despite the fact that many different tactics have been used to manage it. The benefits and drawbacks of these diverse approaches are discussed by the authors. Major fungicides' modes of action and methods for resistance to them were also described. The data summarized in this review will help to understand better Bakanae disease situations and aid in the creation of a more successful management strategy for the disease.